La pedagogía intercultural en los territorios indígenas de Costa Rica - Torres Hernández, Rodrigo (2007)
The article comments about the necessity of building intercultural pedagologic strategies jointly, in order to revitalize mother tongues and cultures of Costa Rican indigenous. This proposal is part of the project carry out by the Education Rural Department, which works with culture and mother tongue teachers in the community of Suretka, Talamanca.